Development of life marker chip technology for in-situ life detection on Mars - Wilson, P. K. (Cranfield University, 2007)
The European Space Agency (ESA) is currently developing its flagship Life Detection Mission, ExoMars, which is scheduled to fly to Mars in 2013. The primary goal of this mission is to compliment the Phoenix NASA mission in confirming the presence of organic material on Mars, and, for the first time, analyse this organic material to determine the presence of organic species indicative of presence of past or present Life. One of the proposed Life detection technologies is the Life Marker Chip (LMC), which uses immunoassays with fluorescent readout to detect small organics and proteins in a microarray format within microfluidic channel structures. This PhD thesis encompasses the work done by the author on the development of the SMILE LMC during the period prior to, and during part of the first phase of, the Life Marker Chip Technology Readiness Level Upgrade Study funded by ESA from 2005 and 2007. Cont/d.